A dromaeosaurid-like claw from the Upper Cretaceous of southern France. (2nd November 2022) - Santos Brilhante, Natan; de França, Tainá Constância; Castro, Fabiano; Sanches da Costa, Leandro; Currie, Philip J.; Kugland de Azevedo, Sergio Alex; Delcourt, Rafael
ABSTRACT: Dromaeosaurids are poorly known in Europe and their fossil records are mostly postcranial remains. To date, the French faunal records of the family Dromaeosauridae include two taxa: Pyroraptor olympius and Variraptor mechinorum . Nevertheless, their taxonomic validity and phylogenetic relationships as dromaeosaurids are controversial. Here, we report a new record of a dromaeosaurid-like pedal ungual from the 'Grès à Reptiles' Formation (Campanian-Maastrichtian) of the Upper Cretaceous of southern France. The French specimen was assigned to cf. Dromaeosauridae on the basis of an extensive qualitative analysis. The new specimen has a strongly curved morphology with a tall, narrow cross-section, which is one of the most characteristic anatomical features of the family. Direct comparison reveals that the claw is similar to that of Pyroraptor olympius (MNHN BO001) from a stratigraphically correlated locality.